The Many Hidden Faces of Gallbladder Carcinoma on CT and MRI Imaging-From A to Z - Neculoiu D, Neculoiu, LCș Popa, RM; Manea, RM (MDPIMDPI AG, Grosspeteranlage 5, CH-4052 BASEL, SWITZERLAND, 2024)
Gallbladder carcinoma represents the most aggressive biliary tract cancer and the sixth most common gastrointestinal malignancy. The diagnosis is a challenging clinical task due to its clinical presentation, which is often non-specific, mimicking a heterogeneous group of diseases, as well as benign processes such as complicated cholecystitis, xanthogranulomatous cholecystitis, adenomyomatosis, porcelain gallbladder or metastasis to the gallbladder (most frequently derived from melanoma, renal cell carcinoma). Risk factors include gallstones, carcinogen exposure, porcelain gallbladder, typhoid carrier state, gallbladder polyps and abnormal pancreaticobiliary ductal junction. Typical imaging features on CT or MRI reveal three major patterns: asymmetric focal or diffuse wall-thickening of the gallbladder, a solid mass that replaces the gallbladder and invades the adjacent organs or as an intraluminal enhancement mass arising predominantly from the gallbladder fundus. The tumor can spread to the liver, the adjacent internal organs and lymph nodes. Depending on the disease stage, surgical resection is the curative treatment option in early stages and adjuvant combination chemotherapy at advanced stages. The purpose of this scientific paper is to fully illustrate and evaluate, through multimodality imaging findings (CT and MRI), different presentations and imaging scenarios of gallbladder cancer in six patients and thoroughly analyze the risk factors, patterns of spread and differential diagnosis regarding each particular case.